Getting started with open-hardware: Development and control of microfluidic devices - da Costa, Eric Tavares; Mora, Maria F.; Willis, Peter A.; do Lago, Claudimir L.; Jiao, Hong; Garcia, Carlos D. (Electrophoresis, 2014)
Understanding basic concepts of electronics and computer programming allows researchers to get the most out of the equipment found in their laboratories. Although a number of platforms have been specifically designed for the general public and are supported by a vast array of on‐line tutorials, this subject is not normally included in university chemistry curricula. Aiming to provide the basic concepts of hardware and software, this article is focused on the design and use of a simple module to control a series of PDMS‐based valves. The module is based on a low‐cost microprocessor (Teensy) and open‐source software (Arduino). The microvalves were fabricated using thin sheets of PDMS and patterned using CO2 laser engraving, providing a simple and efficient way to fabricate devices without the traditional photolithographic process or facilities. Synchronization of valve control enabled the development of two simple devices to perform injection (1.6 ± 0.4 μL/stroke) and mixing of different solutions. Furthermore, a practical demonstration of the utility of this system for microscale chemical sample handling and analysis was achieved performing an on‐chip acid–base titration, followed by conductivity detection with an open‐source low‐cost detection system. Overall, the system provided a very reproducible (98%) platform to perform fluid delivery at the microfluidic scale.